Case Report of Kikuchi-Fujimoto Disease from Sub-Saharan Africa: An Important Mimic of Tuberculous Lymphadenitis - Karishma Sharma; Fredrick Otieno; Reena Shah (Case Reports in Medicine)
Kikuchi-Fujimoto disease (KFD) is a rare form of painful lymphadenopathy, usually cervical, which is more common in Southeast Asia and rarely reported from Africa. Symptoms are usually nonspecific (fever, night sweats, etc.), and can mimic more common diseases such as tuberculosis (TB) in endemic areas. We report a case of a 29-year-old black African woman who was admitted with headache, neck pain, fever, and lymphadenopathy. She was found to have aseptic meningitis, eventually attributed to TB based on cervical node biopsy, although further histology suggested KFD. Blood tests for systemic lupus erythematosus (SLE) were negative; she had already been commenced on anti-TB treatment and had responded well and so was continued with this therapy. She was also later diagnosed with Hashimoto’s thyroiditis 3 months after her diagnosis of KFD. Five months after stopping TB treatment, she was readmitted with the same symptoms and associated painless lymphadenopathy. Repeat biopsy was morphologically similar to that of 2017, and repeat evaluation confirmed SLE. She has since been managed by a rheumatologist and continues to do well.